Ion-conducting materials, electrolytes including ion-conducting materials, and methods of forming

By adopting composite metal halide materials and specific process treatments, the problems of poor stability and difficulty in mass production of solid lithium battery electrolyte materials at high temperatures are solved, and the electrochemical stability and conductivity are improved.

CN119786709APending Publication Date: 2025-04-08SAINT GOBAIN CERAMICS & PLASTICS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411963435.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-04-14
Filing Date
2021-04-14
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The electrolyte materials of existing solid-state lithium batteries have poor stability at high temperatures and are difficult to produce on a large scale, which affects the energy density and safety of lithium batteries.

Method used

A composite metal halide material is used to form a solid ionic conductive material with improved properties by a specific stoichiometric ratio and dopant. The process includes forming a reaction mixture, drying and decomposing ammonium halide to obtain a composite metal halide of high purity and low impurity.

Benefits of technology

The electrochemical stability and ionic conductivity of solid-state lithium battery electrolyte materials are improved, production costs are reduced, and the purity and properties of the materials are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786709A_ABST
    Figure CN119786709A_ABST
Patent Text Reader

Abstract

The invention relates to ion conductive materials, electrolytes including ion conductive materials, and methods of forming. The solid ionically conductive material may include a composite metal halide. The composite metal halide may include at least one alkali metal element. In one embodiment, the solid ionically conductive material including the composite metal halide may be a single crystal. In another embodiment, the ion conductive material including the composite metal halide may be a crystalline material having a particular crystallographic orientation. A solid electrolyte may include the ion conductive material including the composite metal halide.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention patent application with application date of April 14, 2021, application number 202180027337.X, and name “Ionic conductive materials, electrolytes including ionic conductive materials, and formation methods”. Technical Field

[0002] The following relates to a solid ion conductive material, an electrolyte comprising the ion conductive material, and a method for forming the solid ion conductive material, and particularly to a solid ion conductive material comprising a composite metal halide, an electrolyte comprising the solid ion conductive material, and a method for forming the solid ion conductive material. Background Art

[0003] Compared with conventional lithium-ion batteries, solid-state lithium batteries are expected to provide higher energy density and faster charging time and reduce safety issues by enabling lithium metal anodes. Current solid electrolyte materials include oxides, halides, sulfides, fluorides and solid polymer electrolytes.

[0004] Oxide-based materials have been considered safe and have good chemical and electrochemical stability. The synthesis of these compounds usually uses high temperatures above 1000°C to 1200°C. Oxide-based materials are generally dense, rigid and brittle, with ionic conductivity (IC) at room temperature. RT ) up to 1.0mS / cm.

[0005] Halogenated compounds (such as chlorides and bromides) are generally safe and have good chemical and electrochemical stability, deformability and plasticity, allowing relatively high compatibility with active electrode materials. Some Li3YCl6 (LYC) and Li3YBr6 (LYB) electrolytes have shown room temperature ionic conductivity IC above 1 mS / cm. RT Halides are generally hygroscopic and form hydrates or hydrolyze when exposed to moisture. Halide solid electrolytes such as LYC and LYB are synthesized by using a solid-state synthesis method based on high-energy ball milling. The synthesis is also challenging for large-scale production applications because of the use of expensive binary halogenation reactants and / or high temperature annealing.

[0006] Fluorides are very similar to oxides in their physical, chemical, and electrochemical properties, but typically have IC values ​​below 1 mS / cm RT value.

[0007] Sulfides have relatively high ionic conductivity. For example, IC RTIt can be as high as 25mS / cm, while commercially relevant sulfide or thiophosphate solid electrolytes can reach 2mS / cm to 10mS / cm. Sulfide materials are mechanically softer and deformable. However, sulfide materials tend to have poor electrochemical stability and pose safety issues due to the risk of releasing toxic H2S gas when reacting unexpectedly with water and heat. In addition, high surface area sulfide solid electrolyte powders have a particularly high H2S risk due to their increased reactivity even at ambient humidity.

[0008] Solid polymer electrolytes containing lithium salts generally have relatively low ICRT values ​​and electrochemical stability.

[0009] The industry continues to demand improved solid electrolyte materials. Summary of the invention

[0010] The present invention relates to a solid ion conductive material, comprising:

[0011] Composite metal halide materials,

[0012] The composite metal halide material is composed of M 3-z (Me k+ ) f X 3-z+k*f represents, where:

[0013] -3≤z<3;

[0014] 2≤k<6;

[0015] 0≤f≤1;

[0016] M includes alkali metal elements;

[0017] Me includes a divalent metal element, a trivalent metal element, a tetravalent metal element, a pentavalent metal element, a hexavalent metal element, or any combination thereof; and X includes a halogen; and

[0018] The composite metal halide material comprises a charge-neutral Me x N k or M x N, wherein x is the valence of nitrogen N, and k is the valence of Me. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The present disclosure may be better understood, and its numerous features and advantages made apparent to those skilled in the art by referencing the accompanying drawings.

[0020] Figure 1 Included is a flow chart illustrating a method of forming a solid ion conducting material according to one embodiment.

[0021] Figure 2 Included is a flow chart illustrating a method of forming a solid ion conducting material according to one embodiment.

[0022] Figure 3A Included is a cross-sectional illustration of a solid ion conducting material according to one embodiment.

[0023] Figure 3B include Figure 3A Illustration of exemplary crystallographic orientations of solid ion-conducting materials.

[0024] Figure 4 Included is a flow chart illustrating a method of forming a solid ion conducting material according to one embodiment.

[0025] Figure 5 Included is a cross-sectional illustration of a portion of a solid-state battery according to one embodiment.

[0026] Those skilled in the art will appreciate that, for simplicity and clarity, the elements shown in the figures are not necessarily drawn to scale. For example, the size of some elements in the figures may be enlarged relative to other elements to help enhance understanding of the embodiments of the present invention. In different figures, the same reference symbols are used to represent similar or identical items. DETAILED DESCRIPTION

[0027] The following description in conjunction with the accompanying drawings is provided to help understand the teachings disclosed herein. The following discussion will focus on specific implementations and embodiments of the teachings. This emphasis is provided to help describe the teachings and should not be interpreted as a limitation on the scope or applicability of the teachings.

[0028] As used herein, the terms "consisting of," "including," "comprising," "having," "having" or any other variation thereof are intended to cover a non-exclusive inclusion. For example, a process, method, article, or apparatus that includes a list of features is not necessarily limited to only those features, but may include other features not expressly listed or inherent to such process, method, article, or apparatus. In addition, unless expressly stated otherwise, "or" refers to an inclusive "or" and not an exclusive "or." For example, any of the following may satisfy condition A or B: A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and both A and B are true (or exist).

[0029] The elements and components described herein are described using "a" or "an". This is done only for convenience and to give a general sense of the scope of the invention. Unless otherwise apparent, this description should be understood to include one or at least one, and the singular also includes the plural, or vice versa.

[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present invention belongs. The materials, methods, and examples are illustrative only and not limiting.

[0031] Embodiments herein relate to a solid ion conducting material comprising a composite metal halide, wherein the metal may include at least one alkali metal element. In one embodiment, the solid ion conducting material may include a dopant comprising ammonium. In another embodiment, the solid ion conducting material may include a crystalline material, and in a particular embodiment may include an oriented crystalline material, such as a single crystal or an oriented ceramic having a particular crystallographic orientation. Compared to conventional metal halide materials, the solid ion conducting material may have improved properties, such as purity, bulk ionic conductivity, electrochemical stability, or any combination thereof. In an embodiment, the solid ion conducting material may be used to form an electrolyte, an anode and / or a cathode, or another component of an electrochemical device. In a particular embodiment, the solid ion conducting material may be a suitable component of a solid-state lithium battery.

[0032] Embodiments relate to methods of forming ion conducting materials. The methods may allow for the formation of ion conducting materials having improved properties such as purity, ionic conductivity, electrochemical stability, or combinations thereof. The methods may also allow for improved formation of ion conducting materials. The methods may be suitable for mass production of ion conducting materials in an economical and efficient manner.

[0033] refer to Figure 1 , a method 100 for forming a solid ion conducting material is shown.

[0034] Method 100 is different from conventional solid-state synthesis for forming complex metal halides. Conventional methods utilize high-energy ball milling or directly heating a reactant mixture (e.g., a simple metal halide) at a temperature close to or below the melting point of the metal halide to perform a solid-state reaction. Because the probability of a single isolated particle in the mixture reacting decreases as the reaction proceeds, it is theoretically necessary to take an infinite amount of time to achieve 100.00% reaction completion. Therefore, it is understandable that the reaction products produced by conventional solid-state synthesis based on high-energy ball milling have a higher concentration of impurities, such as simple metal halides (e.g., lithium halides and / or yttrium halides), due to the incomplete reaction of the simple metal halides.

[0035] It is also worth noting that the conventional composite halide synthesis based on the ammonium-halide route may not be suitable for forming composite metal halides. Metal halides are generally used as starting materials. Since some trivalent metal halides and tetravalent metal halides, and particularly rare earth halides, tend to form stable metal halide hydrates, it is difficult to completely remove water molecules from those hydrates. Increasing the temperature may lead to the formation of higher concentrations of unwanted metal halide oxides or metal oxyhydroxide halide compounds. In addition, metal halide hydrates and metal oxyhalides, particularly those including rare earth metals, are fairly stable compounds and are unlikely to form composite compound phases containing high concentrations of Li, such as Li3RE(OX)Cl3, where X is a halogen other than Cl. In addition, those composite compounds will be unstable and may decompose into simple compounds.

[0036] The methods described in the embodiments of the present disclosure overcome the above-mentioned problems.

[0037] Method 100 may begin at block 102. A reaction mixture may be formed including a starting material. In one embodiment, the starting material may include an ammonium halide NH4X, wherein X includes Cl, Br, I, F, or any combination thereof. The starting material may further include one or more metal compounds, wherein the metal may include an alkali element, an alkaline earth element, a transition metal element, a lanthanide element, a rare earth element, or any combination thereof.

[0038] In certain embodiments, the metal compound can be non-hygroscopic. In one aspect, the metal compound can include a metal in the form of an oxide, carbonate, sulfate, hydrate, hydroxide, oxalate, acetate, nitrate, or any combination thereof. In certain aspects, the starting material can include more than one metal oxide. For example, the starting material can include Me2O k , wherein Me can be a divalent metal, a trivalent metal, a tetravalent metal, a pentavalent metal, or a hexavalent metal; k is the valence of the metal; and 2≤k≤6. In a specific example, Me can include rare earth elements including Ce, Dy, Er, Eu, Gd, Ho, La, Lu, Nd, Pr, Pm, Sm, Sc, Tb, Tm, Yb, Sc and Y, In, Zn, alkali metal elements, Hf, Zr, or any combination thereof. In a more specific example, the starting material can include one or more of rare earth oxides or hydroxides or carbonates, ZrO2 or Zr(OH)4 or Zr(CO3)2 or Zr(OH)2CO3·ZrO2 or any combination thereof.

[0039] In another aspect, the starting materials can include alkali metal compounds such as lithium carbonate, sodium carbonate, cesium carbonate, or combinations thereof. The starting materials can further include an acid to facilitate acid synthesis in an aqueous, alcoholic, or other polar molecular liquid solution.

[0040] In another specific case, the metal compound can consist of an alkali metal compound. For example, the starting materials can include alkali metal halides (e.g., NaCl, CsCl, and LiCl) and do not contain compounds including Me.

[0041] In embodiments, the starting materials can be mixed in stoichiometric ratios. In other embodiments, the ratios between the starting materials can allow for the formation of non-stoichiometric complex metal halides.

[0042] In an exemplary embodiment, a reaction mixture can be formed that includes NH4X, one or more rare earth metal oxides (hereinafter referred to as "RE2O3"), lithium carbonate, and hydrochloric acid or hydrobromic acid. The reaction is shown below, demonstrating the starting materials and reaction products in an aqueous solution.

[0043] 3*Li2CO3 + RE2O3 + 12*HX + 6*NH4X ---> 2*(NH4)3REX6 + 6*LiX + 6*H2O + 3*CO2

[0044] The above reaction is an example intended to aid in understanding Method 100. According to the present application, one skilled in the art will understand that another alkali metal compound such as Na2CO3 or NaCl can be used as a starting material. Similarly, oxides of non-rare earth elements such as Fe2O3 can be added to the reaction. One skilled in the art further recognizes that as the starting materials change, the reaction products will change accordingly.

[0045] In a specific embodiment, Method 100 can include chemically replacing the water (i.e., moisture) in the hydrated salt containing MeX with NH4X. k In one aspect, the method can include forming (NH4) n Me k+ X n+k , where n > 0; and 2 ≤ k < 6. In certain cases, 0 < n ≤ 3. In certain cases, n can be 0.33, 0.5, 1, 1.5, 2, 3, or 4, depending on what Me is. In the above reaction, hydrated rare earth halides can be formed as intermediate products, and the water in the hydrate can be replaced by NH4X to form (NH4)3REX6, with the advantage that no hydrated compounds are formed, allowing for operation and maintaining a hydroxide-free halide phase. As further shown, alkali metal halides such as LiX are also formed.

[0046] In one embodiment, the mixture of reaction products can be filtered to remove larger particles to facilitate subsequent reactions in the solid state. Larger particles can include impurities with any starting materials, residual particles of starting materials, carbon, or any combination thereof.

[0047] The method 100 may continue with the steps of block 104. In one embodiment, the mixture of reaction products may be dried to promote the (NH4) n Me k+ X n+k Solid state reaction of an alkali metal halide MX, wherein M is an alkali metal element. Drying can be carried out in air or dry air and / or under vacuum or reduced pressure, such as 100 mbar, 40 mbar, 1 mbar or even 0.01 mbar. In some cases, N2 or Ar flow can be used to promote the removal of water. In another example, heating can be used to facilitate the evaporation of water. The heating temperature can be 100°C to 160°C. Drying can be carried out until traces of water, such as 1 wt% to 3 wt%, are left in the mixture.

[0048] In one embodiment, method 100 may include performing (NH4) n Me k+ X n+k In one specific example, the reaction products shown above can be subjected to a solid-state reaction of (NH4)3REX6 and LiX. In another embodiment, the method 100 may include forming (NH4) n M 3-z Me k+ X 3+n+k-z , where -3≤z=<3. Where z=0, (NH4) n M 3-z Me k+ X 3+n+k-z is stoichiometric. When z is not zero, (NH4) n M 3-z Me k+ X 3+n+k-z is non-stoichiometric. In certain cases, 0≤z<1. In yet another case, method 100 may include forming M 3-z (Me k+ ) f X 3-z+k*f , where -3≤z<3; 2≤k<6; 0≤f≤1.

[0049] Method 100 may continue with the steps of block 106. In one embodiment, forming the ion conductive material may include decomposing the ammonium halide. In one aspect, the decomposing may include separating the composite metal halide phase from the ammonium halide phase. In another aspect, forming the ion conductive material may further include the escape of the ammonium halide.

[0050] In one aspect, the decomposition can be performed in a crucible made of a material that is inert to the reactants and products. For example, the crucible can be made of quartz, alumina, silica-alumina, BN, glassy carbon, or graphite. In a particular embodiment, the graphite can have a pyrolytic carbon coating.

[0051] In another aspect, the decomposition can be carried out in a dry and neutral atmosphere, such as air or dry air. An inert gas such as N2 or Ar can be used to facilitate the process.

[0052] In yet another aspect, the decomposition can be carried out for at least 15 minutes to at most 24 hours. In one aspect, the solid solution can be heated to a temperature in the range of 350°C to 800°C to sublime the ammonium halide partially or completely. In some cases, the sublimation of NH4X can be monitored by weighing the escaping NH4X collected and condensed on the other side.

[0053] In yet another aspect, sublimation can be performed so that most of the ammonium halide, such as at least 60 wt %, at least 80 wt % or at least 90 wt % of the ammonium halide can be removed compared to the weight of the ammonium halide initially added. In yet another aspect, the aluminum halide can be removed substantially by sublimation. In another aspect, sublimation can be performed so that the residual ammonium halide can be contained by the ion conductive material.

[0054] In another aspect, the decomposition of the ammonium-containing complex metal halide can help remove reaction products other than the complex metal halide from the solid solution. For example, water, CO2, ammonia and halogens can be evaporated.

[0055] Alternatively, the starting materials can be heated at a higher temperature to form the ammonium-containing complex metal halide in one step. An exemplary one-step reaction is shown below.

[0056] 3*Li2CO3+RE2O3+18*NH4Br---->2*(NH4)3Li3REBr9+6*H2O+3*CO2+12*NH3.

[0057] In particular, the heating can be performed so that the decomposition of the ammonium and the solid state reaction can proceed simultaneously. For example, the heating temperature can be in the range of 250°C to 650°C or up to 800°C to allow the formation of a solid solution and sublimation of the ammonium halide. It has been noted that when using a one-step synthesis to form a complex metal halide, a relatively high content of oxyhalide may be generated.

[0058] In another embodiment, method 100 may include forming an ionically conductive material including a complex metal halide. In one aspect, the complex metal halide may be composed of M 3-z Me k+ X 3-z+k In another aspect, the complex metal halide is composed of M 3-z (Me k+ ) f X 3-z+k*f Represents, where 0≤f≤1.

[0059] In one aspect, cooling can be performed after decomposition. For example, cooling can be performed in air, dry air or nitrogen environment. In another example, the cooling temperature can be lower than 200°C, such as up to 100°C, up to 70°C, up to 50°C or up to 30°C. In a specific embodiment, cooling can be performed at room temperature (e.g., 20°C to 25°C) in a dry atmosphere. Optionally, Ar or N2 can be used to promote cooling.

[0060] In another aspect, an ionically conductive material including a complex metal halide can be formed after cooling.

[0061] In one embodiment, a composite metal halide including a specific content of residual ammonium halide can be formed. In at least one example, the ion conductive material can include at least 2 ppm of ammonium halide accounting for the total weight of the composite metal halide, such as at least 10 ppm, at least 100 ppm, at least 300 ppm, at least 500 ppm, at least 0.2 wt %, at least 0.5 wt % or at least 1 wt % of ammonium halide accounting for the total weight of the composite metal halide. In another example, the ion conductive material can include ammonium halide accounting for up to 5 wt % of the weight of the composite metal halide, such as up to 3 wt %. It should be understood that the composite metal halide may include a residual ammonium halide content within a range including any minimum or maximum value mentioned herein. In at least one example, the composite metal halide may be substantially free of ammonium halide.

[0062] In one embodiment, the ion conductive material can be in the form of a powder, such as particles comprising a complex metal halide. In one aspect, the powder can have an average particle size (D50) of at least 0.1 microns, such as at least 0.3 microns, at least 0.5 microns, or at least 1 micron. In another aspect, the average particle size can be at most 1 mm, at most 800 microns, at most 500 microns, at most 200 microns, at most 100 microns, at most 50 microns, at most 10 microns, at most 5 microns, or at most 1 micron. In certain cases, the powder may include particles having an average particle size within a range including any minimum and maximum values ​​mentioned herein. In another aspect, the powder may include agglomerated particles.

[0063] In yet another aspect, the particles can have a specific shape that can facilitate the formation and performance improvement of the electrolyte and / or electrode. For example, the particles can be spherical or elongated. In another example, the particles can have the shape of a rod, a sheet, or a needle. The shape of the particles can be selected based on the 2D or 1D anisotropy of the ionic conductivity of the composite metal halide.

[0064] In another aspect, the powder can include particles having a particular average length: width aspect ratio to facilitate the formation of electrolytes and / or electrodes having improved ionic conductivity. In one example, the average aspect ratio can be at least 1, such as at least 1.2, at least 1.5, at least 2, at least 2.3, at least 2.5, at least 2.8, or at least 3. In another example, the average aspect ratio can be at most 30, at most 25, at most 22, at most 20, at most 15, at most 12, at most 10, at most 8, at most 5, or at most 4. In addition, the particles can have an average aspect ratio within a range including any minimum and maximum values ​​mentioned herein.

[0065] In one embodiment, the ion-conducting material may include certain impurities at low levels. The impurities may include simple metal halides, including Me k+ X k Such as rare earth halides, alkali halides such as LiCl and / or NaCl, metal nitrides such as M3N, and Me x N y , or any combination thereof. The coefficients x and y are charge neutral Me x N y In another embodiment, the impurity may include amide (NH2), imide (NH), hydroxide (OH), ammonia (NH3), or any combination thereof.

[0066] In one embodiment, the complex metal halide may be composed of M 3-z (Me k+ ) f X 3-z+k*f, wherein -3≤z≤3; 2≤k<6; and 0≤f≤1. In certain aspects, f is not zero. In certain aspects, z<3. In still certain cases, when f=0, z may not be 3. M may include an alkali metal element; Me may include a divalent metal element, a trivalent metal element, a tetravalent metal element, a pentavalent metal element, a hexavalent metal element, or any combination thereof; and X may include a halogen.

[0067] In another embodiment, the complex metal halide may be composed of M 3-z Me k+ X 3-z+k = , wherein -3≤z≤3; M may include an alkali metal element; Me may include a divalent metal element, a trivalent metal element, a tetravalent metal element, a pentavalent metal element, a hexavalent metal element, or any combination thereof; and X may include a halogen. In a specific aspect, z<3.

[0068] In another aspect, M may be composed of one or more alkali metal elements including Li, Na, Cs and Rb. In yet another aspect, M may include Li. For example, M may consist of Li. In another aspect, M may include Li and another alkali metal. For example, M may include Li and at least one of Na, Cs and Rb. In another case, M may consist of Li and at least one of Na, Cs and Rb. In a more specific case, M may consist of a combination of Li and Na. In another aspect, M may include a combination of Na or Na with at least one of Cs and Rb. In another case, M may consist of at least one of Na and Cs.

[0069] In certain embodiments, Na may account for up to 40 mol% of M, such as up to 34 mol% of M. For example, M may include 0 mol% to 40 mol% Na. In certain examples, M may include up to 20 mol% Na, or even more particularly, up to 10 mol% Na. In at least one case, Na may account for 40 mol% to 100 mol% of M.

[0070] In yet another specific embodiment, Li may account for at least 50 mol%, or at least 60 mol%, or at least 66 mol%, or at least 75 mol% of M. In a specific example, M may include 60 mol% to 100 mol% Li.

[0071] In another case, Cs can account for at least 25 mol% of M, such as at least 30 mol%, at least 40 mol%, or at least 50 mol% of M. In another case, Cs can account for at most 50 mol%, or at most 40 mol%, or at most 30 mol%, or at most 20 mol% or at most 10 mol% of M. In a specific case, Cs can account for at most 1 mol% of M.

[0072] In one embodiment, the complex metal halide can be represented by (Li 1-d ,Na d )2Li 1-z Me k+ X 3+k-z where 0 < d < 1; -0.95 ≤ z ≤ 0.95; Me can include divalent metal elements, trivalent metal elements, tetravalent metal elements, pentavalent metal elements, hexavalent metal elements, or any combination thereof; and X can include halogens.

[0073] In one embodiment, the complex metal halide can be represented by (Li 1-d-e ,Na d ,M' e )2Li 1-z’ (Me k+ ) f X 3+k*f-z where 0 ≤ d ≤ 1; 0 ≤ e < 1; -3 ≤ z' ≤ 3; 2 ≤ k < 6; 0 ≤ f ≤ 1; M' can include at least one of K, Rb, and Cs; and Me can include divalent metal elements, trivalent metal elements, tetravalent metal elements, pentavalent metal elements, hexavalent metal elements, or any combination thereof; and X can include halogens. In a specific aspect, z' < 3. In a specific aspect, d + e > 0. In a specific aspect, f is not zero. In a more specific aspect, e = 0 and d is not zero.

[0074] In one aspect, d can be at least 0.01 or at least 0.05 or at least 0.1 or at least 0.2. In another aspect, d can be at most 0.8 or at most 0.5. In a specific aspect, d can be within a range including any minimum and maximum values.

[0075] In one aspect, e can be at least 0.01 or at least 0.05 or at least 0.1 or at least 0.2. In another aspect, e can be at most 0.8 or at most 0.5. In a specific aspect, e can be within a range including any minimum and maximum values.

[0076] In one embodiment, the complex metal halide can be represented by Li 3-z Me k+ X 3-z+kRepresents, wherein -0.95≤z=<0.95; and Me may include a divalent metal element, a trivalent metal element, a tetravalent metal element, a pentavalent metal element, a hexavalent metal element, or any combination thereof; and X may include a halogen.

[0077] In one aspect, z may be at most 0.5, such as at most 0.3 or at most 0.2. In another aspect, z may be at least -0.5 or at least -0.2. In a particular example, z may be within a range including any minimum and maximum values ​​mentioned herein. When z is not 0, the complex metal halide may be non-stoichiometric. When z is 0, the complex metal halide may be stoichiometric.

[0078] Exemplary divalent metal elements may include alkaline earth metal elements, such as Mg and / or Ca, Zn, or any combination thereof. In a specific embodiment, Me may include Zn, Ca, or any combination thereof. In a specific embodiment, when the halogen includes Cl or consists of Cl, ions with a relatively small radius (such as Zn and Mg) may be particularly suitable; and when the halogen includes Br or consists of Br, ions with a relatively large radius (such as Ca) may be particularly suitable. In another specific embodiment, substitution ions containing radii larger than alkaline ions may help to expand the ion conduction channels in the electrolyte material. For example, Me may include Ca and Y, wherein Ca may be suitable for partially replacing Y. In another embodiment, divalent elements with relatively light weight (such as Mg, Zn, and Ca) may be preferred. In some cases, replacing Y with Sr or Ba may result in the formation of SrX2 or BaX2 compounds, which may be impurities that affect the bulk ionic conductivity of the composite metal halide.

[0079] Exemplary trivalent metal elements may include rare earth elements, trivalent metals other than rare earth elements, such as In, Ga, Al, or Bi, or any combination thereof. In a specific example, Me may include Sc, Y, La, Gd, or any combination thereof. In a more specific case, Me may include Y, Gd, or a combination thereof.

[0080] Exemplary tetravalent metal elements may include Zr, Hf, Ti, Sn, Ge, Th, or any combination thereof. In a specific example, Me may include Zr and Hf. In another specific example, Me may include Zr.

[0081] Exemplary pentavalent elements may include Ta, Nb, W, Sb, or any combination thereof.

[0082] In one aspect, Me can include rare earth elements, alkaline earth metal elements, 3d transition metals, Zn, Zr, Hf, Ti, Sn, Th, Ge Ta, Nb, Mo, W, Sb, In, Bi, Sc, Yb, Al, Ga, Fe, or any combination thereof.

[0083] In yet another aspect, Me can include rare earth elements, Zr, or any combination thereof.

[0084] In another aspect, Me can include Y, Ce, Gd, Er, Zr, La, Yb, In, Mg, Zn, or any combination thereof.

[0085] In the case where Me includes more than one metal element, k can be the average of the total valence of each Me metal element. For example, when Me includes equimolar amounts of trivalent elements and tetravalent elements, k=(3+4) / 2=3.5. In certain aspects, k can be 3 or 4 or 5.

[0086] In yet another aspect, Me may include rare earth elements (including Y, Gd, La and / or Sc), alkaline earth elements, 3d transition metals, Zn, Zr, Hf, Ti, Sn, Th, Ta, Nb, Mo, W, Sb, In, Bi, Al, Ga, Ge, or any combination thereof. In a specific example, Me may include Y, Gd, Zr, or any combination thereof. In a specific case, Me may include Y partially substituted by another Me element. For example, Y may be substituted by another Me element of a specific content, which may be beneficial to improve the crystal structure and properties of the composite metal halide. In a specific example, Me may include up to 70 mol% of Y and 5 mol% to 30 mol% of the substituted Me element. In yet another example, Y may be partially substituted by a Me element having a suitable effective ionic radius, which may allow the formation of a stable phase of a composite metal halide. In a specific example, the Me element may have an ionic radius less than the effective ionic radius La (103.2A) and at least similar to the effective ionic radius Li (0.76A). In a more specific example, the Me element may have an effective ionic radius ranging from 0.76 ű5% to 93.5 ű5%.

[0087] In a specific embodiment, Me may consist of Gd, Y, Ce, Er, Zr, Yb, or any combination thereof. For example, Me may consist of Y. In another example, Me may consist of Y and at least one of Ce, Er, Zr, and Gd. In yet another example, Me may consist of Yb and Ce. In another example, Me may consist of two or more of In, Y, Zr, Hf, Sc, Zn, and Mg.

[0088] In one aspect, X may include at least one of Cl, Br, I, and F. For example, X may include Cl or Br. In another example, X may include F. In another example, X may include at least two of Cl, Br, and I. In yet another example, X may include all of Cl, Br, and I.

[0089] In one aspect, X may include elements other than halogens. In some embodiments, X may include anionic groups other than halogens. Such anionic groups may include amides (-NH2), -(NH) 0.5 (imide), hydroxide (-OH), -BF4, -BH4 (borohydride), or a combination thereof. Anionic groups may be included as impurities or dopants.

[0090] In certain aspects, X may consist of at least one of F, Cl, Br and I and optionally an anionic group including -NH2 (amide), -(NH) 0.5 (imide), -OH (hydride), -BH4 (borohydride), -BF4 group or any combination thereof. For example, X can be composed of one or both of Cl and Br and at least one anionic group. In another example, X can be composed of F and at least one anionic group. In at least one embodiment, X can be one or more halogens.

[0091] In a specific example, M may be Li, Me may be a combination of In, Mg, Zr, and Sc, and X may be Cl or a combination of Cl and an anionic group.

[0092] In another specific example, M may be Li, Me may be Y, Zr, and Hf, and X may be Cl or a combination of Cl and an anionic group.

[0093] In another specific example, M may be Na, Me may be Zr, and X may be Cl or a combination of Cl and an anionic group.

[0094] In a specific embodiment, the complex metal halide is composed of (Li (1-d-e) ,Na (d) ,M' (e) )2Li (1-z) Me 3 + (1-u-p-q-r) Me 4+ (u) Me 2+ (p) Me 5+ (q) Me 6+ (r) (Cl(1-y-w) Br (y) I (w) ) (6+u-p+2q+3r-z) represents, where 0 ≤ d ≤ 1; 0 ≤ e < 1; -3 ≤ z ≤ 3; M' includes at least one of K, Rb, Cs; M 3+ includes rare earth elements, In, Bi, Sc, Y, Al, Ga, or any combination thereof; Me 4+ is Zr 4+ , Hf 4+ , Ti 4+ , Sn 4+ , Th 4+ , Ge 4+ or any combination thereof; Me 2+ is Mg 2+ , Zn 2+ , Ca 2+ , Yb 2 + , Eu 2+ or any combination thereof; Me 5+ is Ta 5+ , Nb 5+ , W 5+ , Sb 5+ or any combination thereof; Me 6+ is W 6+ , Mo 6+ or any combination thereof; 0 <= w <= 1; 0 <= y <= 1; -0.95 < z < 0.95; 0 <= u < 0.95; 0 <= p < 0.95; 0 <= q < 0.95; and 0 <= r < 0.95.

[0095] In certain aspects, M 3+ can include Y 3+ , Gd 3+ , In 3+ , Er 3+ , Sc 3+ or any combination thereof. In more specific aspects, M 3+ can consist of Y 3+ , Gd 3+ , In 3+ , Er 3+ , Sc 3+ , or any combination thereof.

[0096] In certain aspects, M 4+ can include Zr 4+ , Hf 4+ , Ce 4+ or a combination thereof. In more specific aspects, M 4+ can consist of Zr 4+ , Hf 4+, Ce 4+ or a combination thereof.

[0097] In another specific aspect, any one or more of p, q, r, and u can be 0. In a more specific aspect, p, q, r, and u can all be 0.

[0098] In a specific aspect, k can be 2 or 3 or 4 or 5.

[0099] In another specific aspect, the complex metal halide is represented by (Li (1-d), Na (d) )2Li (1-z) RE (1-u) Zr 4+ (u) (Cl (1-y) Br (y) ) (6+u-z) where 0 < d < 1; 0 < z < 0.95; and 0 <= u < 0.95. In one case, d can be at least 0.0001, at least 0.001, at least 0.005, at least 0.008, at least 0.01, at least 0.02, at least 0.03, at least 0.05, or at least 0.06. In yet another case, d can be at most 0.5, at most 0.3, at most 0.2, at most 0.1, at most 0.08, at most 0.06, at most 0.05, at most 0.04, or at most 0.03. In yet another case, d can be in a range including any minimum and maximum values mentioned herein. For example, 0 < d < 0.05. In yet another case, z can be at least 0.02, at least 0.03, at least 0.05, at least 0.07, at least 0.09, at least 0.1, at least 0.15, at least 0.18, or at least 0.2. In another case, z can be at most 0.5, at most 0.4, at most 0.38, at most 0.35, at most 0.33, at most 0.3, at most 0.28, at most 0.25, at most 0.23, or at most 0.2. Additionally, z can be in a range including any minimum and any maximum values mentioned herein. For example, 0 < z < 0.2. In another case, u can be at least 0.01, at least 0.03, at least 0.05, at least 0.07, at least 0.09, at least 0.1, at least 0.13, at least 0.15, at least 0.18, at least 0.2, at least 0.22, at least 0.25, or at least 0.3. In another case, u can be at most 0.8, at most 0.78, at most 0.75, at most 0.73, at most 0.7, at most 0.68, at most 0.65, at most 0.63, or at most 0.6. Additionally, u can be in a range including any minimum and any maximum values mentioned herein. For example, 0.2 < u < 0.6.

[0100] In a particular embodiment, the complex metal halide may be doped with a dopant. In a particular example, Li may be partially replaced by a dopant. In a more specific example, the dopant may include ammonium, such as ammonium halide NH4X, where X may be Cl, Br, I, F, or any combination thereof.

[0101] In one aspect, the composite metal halide may include ammonium halide at most 20% by weight of the total weight of the composite metal halide, such as ammonium halide at most 15% by weight, at most 10% by weight, at most 8% by weight, at most 5% by weight, or at most 3% by weight of the total weight of the composite metal halide. In another aspect, the ammonium halide may be present in the ion conductive material at a content of at least 10 ppm by mass of the total weight of the composite metal halide, such as at least 100 ppm, at least 500 ppm, at least 0.1% by weight, at least 0.3% by weight, at least 0.5% by weight, at least 0.8% by weight, or at least 1% by weight of the total weight of the composite metal halide. In addition, the composite metal halide may include ammonium halide in a content within a range including any minimum and maximum values ​​mentioned herein.

[0102] refer to Figure 2 , shows an exemplary method 200 for forming a solid ion conducting material. The method 200 may include a method similar to Figure 1 The steps shown in blocks 102 , 104 , and 106 of and described in relation to the steps in an embodiment of method 100 .

[0103] After obtaining the complex metal halide at block 106, method 200 may proceed to the step of block 208. In one embodiment, method 200 may include forming a solid ion conductive material including a single crystal, the single crystal including the complex metal halide. In one aspect, the crystal growth may be performed in a crucible made of a material that is inert to the complex metal halide. For example, the crucible may be made of quartz, alumina, silica-alumina, BN, glassy carbon, or graphite. In a particular embodiment, the graphite may have a pyrolytic carbon coating.

[0104] The complex metal halide obtained by method 100 can be used directly as a charge to form a single crystal. In one aspect, method 200 can include partially or completely melting the complex metal halide. In some cases, a dopant material, such as a metal compound, can be added to the melt to promote the substitution of one or more metal elements of the complex metal halide.

[0105] In yet another aspect, method 200 may include a specific crystal growth rate that can promote the growth of single crystals having macroscopic dimensions, such as single crystal blocks of up to 10 centimeters. For example, the growth rate can be at least 0.2 mm / hour, at least 0.3 mm / hour, or at least 0.5 mm / hour. In another case, the growth rate can be at most 10 mm / hour, such as at most 8 mm / hour, at most 6 mm / hour, at most 5 mm / hour, at most 3 mm / hour, or at most 1 mm / hour. In certain cases, the growth rate can be within a range including any minimum and maximum values ​​mentioned herein.

[0106] In another aspect, method 200 may include cooling the melt. In certain aspects, cooling may be performed in a controlled manner to support the formation of single crystals having complex metal halides. In certain cases, cooling may be facilitated by an external thermal field, wherein the cooling rate is 10°C / hour to 50°C / hour. In another certain case, the starting material of the complex metal halide may form a heterogeneous molten phase due to the presence of impurities such as simple metal halides, and in those cases, the melt may include an excess of a non-stoichiometric mixture including the complex metal halide and a dopant material to facilitate the formation of a stoichiometric single phase crystal under autogenous conditions.

[0107] The single crystal may have the same composition as the complex metal halide formed by method 100 and described in the examples herein.

[0108] Single crystals can be small pieces of a few millimeters or so, or dense blocks, or large ingots up to tens of centimeters in size.

[0109] In one embodiment, when visible impurities and / or parasitic phases are present, the ingot or block may be ground to remove them.

[0110] In yet another embodiment, the single crystal can be ground to form a fine powder having single crystal particles. In one exemplary application, the single crystal particles can be used to form ion-conducting components in an electrochemical device. In another embodiment, the single crystal ingot or block can be sliced ​​into thin slices. For example, the thin slices can have a thickness of 5 microns to 500 microns.

[0111] In a particular embodiment, method 200 may include forming a single crystal having a particular crystallographic orientation. In one aspect, oriented growth of a single crystal may be performed. In a particular aspect, oriented crystal growth may be performed on anisotropic crystals. In an exemplary embodiment, crystallization of spheres or particles having a higher conductivity that are elongated along a crystallographic direction may be performed. In another example, a high temperature gradient, such as 10°C / cm or more, may be applied to promote oriented growth of a single crystal. In yet another example, an X-ray goniometer may be used to identify the orientation of the crystal. In another aspect, for crystals having anisotropy in magnetic permeability or dielectric constant, oriented crystal growth may be performed using a strong permanent magnetic field, solidification under a strong electric field, or any combination thereof. In yet another aspect, the use of a supporting seed layer having a lattice parameter close to that of an oriented ceramic material and solidified in a co-solvent medium may help maintain an oriented polycrystalline structure.

[0112] In another aspect, the single crystal can be sliced ​​so that the crystallographic direction of higher conductivity is along the thickness of the slice.

[0113] In a particular embodiment, the ion-conducting material may include an oriented crystalline material, such as a <hkl>or <hklm>Represents the crystallographic orientation of a single crystal material, where <hkl>or <hklm>The ionic conductivity in the crystallographic orientation of is higher than the ionic conductivity in different crystallographic orientations in which the single crystal may be oriented.

[0114] For example, with <001> In comparison, Li3YBr6 has a crystallographic orientation <100> It can form a material with higher bulk ionic conductivity. <100> Alternatively, a Li3YBr6 single crystal with a crystallographic orientation <001> Li3YBr6 slices with crystallographically oriented cut faces can be formed from a single crystal, and the thickness of the slice is along <100> Crystallographic orientation extension.

[0115] refer to Figure 3A , showing a sheet 300. In one embodiment, the sheet 300 may include a single crystal as described in the embodiments herein. The sheet 300 may have a thickness t extending between major surfaces 302 and 304. Figure 3B Includes an exemplary illustration of the crystallographic orientation of a single crystal. A single crystal can have a layered structure similar to mika, where the length of the layer is along the crystallographic orientation <100> extension, and the stacking of layers is crystallographically oriented <001> Extension. <001> Compared to the crystallographic orientation of a single crystal <100> In certain cases, the thickness t of the sheet 300 may be along the crystallographic orientation <100> In yet another case, one or both of the major surfaces 302 and 304 may be slicing surfaces. Alternatively, the sheet 300 may be formed by oriented crystal growth to have a crystallographic orientation, wherein the thickness t is along the crystallographic orientation <100> extend.

[0116] It is noteworthy that the formation methods of the embodiments herein can allow the formation of ion-conducting materials with higher purity. It is also noteworthy that ion-conducting materials with higher purity can further have improved ion conductivity.

[0117] The formation of complex metal halides using conventional methods such as solid-state reactions based on ball milling can result in higher levels of impurities such as simple metal halides. When a complex metal halide with a high level of simple metal halide contamination or a simple compound is used directly as a starting material to grow a crystal according to the Bridgman-Stockbag method, gradient solidification method, Czech Laski method or Bagdasarov method (horizontal Bridgman method), the melt shows heterogeneous melting and forms a higher level of impurities and parasitic phases in the resulting crystal. The impurities and parasitic phases include one or more simple metal halides such as LiX and Me k+ X k , wherein X is a halogen, such as Cl and / or Br.

[0118] The methods of the embodiments of the present invention can allow the formation of a composite metal halide with a low impurity content. In one embodiment, the composite metal halide can have a total content of simple metal halides accounting for up to 15% by weight of the total weight of the composite metal halide, such as up to 12% by weight, up to 11% by weight, up to 10% by weight, up to 9% by weight, up to 8% by weight, up to 7% by weight, up to 6% by weight, up to 5% by weight, up to 4% by weight, up to 3% by weight, up to 2% by weight, up to 1% by weight or up to 0.5% by weight of the total weight of the composite metal halide. In a specific embodiment, the single crystal of the composite metal halide can be substantially free of simple metal halides. For example, the total content of all simple metal halides can account for less than 0.2% by weight of the weight of the single crystal. It is also worth noting that the composite metal halide of the embodiments of the present invention has a higher bulk ionic conductivity than the composite metal halide manufactured using conventional methods.

[0119] In one embodiment, performing crystal growth can promote further purification of the composite metal halide. In more cases, crystal growth can promote the formation of ion conductive materials with improved bulk ionic conductivity. It is worth noting that the single crystals of the composite metal halide of the embodiments of this invention tend to have further improved bulk ionic conductivity compared to the non-single crystal form (such as powder) of the same composite metal halide of the embodiments of this invention.

[0120] In at least one embodiment, the single crystal of the embodiments of the present invention may include a low content of nitride-based phase impurities. The nitride-based phase may include one or more phases of metal nitrides, metal oxynitrides, metal carbonitrides, or any combination thereof. The formation of the nitride-based phase may be produced by method 100, method 200, or a combination thereof. In some cases, the presence of a specific type of metal nitride, such as Li3N, may help improve the bulk ionic conductivity of the metal halide material.

[0121] refer to Figure 4 , a method 400 for forming an ion conducting material is shown. The process 400 may include Figure 1 All steps shown in and described in the embodiments with respect to method 100 .

[0122] In one embodiment, method 400 may include forming a solid conductive material including an oriented ceramic material. In one aspect, particles of a composite metal halide formed by method 100 may be used. In one case, the particles may have a specific shape, such as an elongated shape, and may be arranged so that the longitudinal axis of the particles extends parallel to the direction of the crystallographic orientation with higher ionic conductivity. In another case, casting, compacting, pressing, heating, molding, or any combination thereof may be used to promote oriented particles. In another case, a magnetic field, an electrical discharge, a thermal gradient, or a combination thereof may be used to promote the crystal orientation of the ceramic particles.

[0123] In another embodiment, method 400 may include performing crystal growth to form an oriented ceramic. In one aspect, method 400 may include forming a melt similar to method 200. In yet another aspect, crystal growth may be performed at a specific growth rate. For example, the growth rate may be at least 8 mm / hour, at least 10 mm / hour, at least 15 mm / hour, or at least 20 mm / hour. In another case, the growth rate may be at most 80 mm / hour, at most 70 mm / hour, at most 60 mm / hour, at most 50 mm / hour, or at most 40 mm / hour. In another case, the growth rate may be within the range of any minimum and maximum values ​​mentioned herein. In another aspect, a thermal gradient may be applied to promote the growth of oriented polycrystalline crystals.

[0124] In one embodiment, method 400 may include forming single crystals as described in the embodiments with respect to method 200. In one aspect, the single crystal pellets may be arranged to form a ceramic ion conductive material having a specific crystallographic orientation. In one example, casting, compacting, pressing, heating, forming, or any combination thereof may be used to promote the formation of a crystal-oriented ceramic ion conductive material. In a particular case, the single crystal particles may be oriented and have a preferred crystallographic orientation.

[0125] In one example, the complex metal halide can be anisotropic, with the crystallographic orientation <100> It has high ionic conductivity and is crystallographically oriented <001> The ionic conductivity is reduced. Figure 3B , single crystals or ceramic pellets of complex metal halide 322 may be arranged as shown to form a crystal-oriented ceramic material.

[0126] The solid ion conductive materials of the embodiments of the present invention can be in different forms. In one embodiment, the ion conductive material may include a powder comprising a composite metal halide. In another embodiment, the ion conductive material may include a single crystal of a composite metal halide. For example, the ion conductive material may include a powder comprising single crystal particles. In another case, the ion conductive material may include a single crystal wafer, a single crystal film, a single crystal block, a single crystal ingot, or other forms of single crystals or any combination thereof. In yet another embodiment, the ion conductive material may include a ceramic material comprising a composite metal halide. For example, the ceramic material may include ceramic particles, single crystal particles, or any combination thereof.

[0127] In another embodiment, the solid ion conducting material can be a polycrystalline, a single crystal, or a crystallographically oriented crystalline material. For example, the solid conducting material can be a single crystal of a composite metal halide. In another case, the solid conducting material can be a ceramic composed of a composite metal halide single crystal. In another case, the solid conducting material can be a crystallographically oriented crystalline material of a composite metal halide.

[0128] In one embodiment, the solid ion conductive material may include a certain amount of impurities. The impurities may exist as a phase different from the complex metal halide, or be compounded with the metal halide in the same phase. For example, a simple metal halide may exist in a phase separate from the complex metal halide. In some cases, the ammonium halide may be completely or partially compounded with the complex metal halide. In particular, compared to conventional solid ion conductive materials that can be represented by the same general formula but formed using methods different from those mentioned in the embodiments of this article, the solid ion conductive material may include improved purity. For example, the sum of the contents of all impurities (also referred to as "total impurity content") may constitute up to 15% by weight of the weight of the complex metal halide in the solid ion conductive material of the embodiments of this article. For example, the total impurity content can be up to 14% by weight of the weight of the composite metal halide, such as up to 13% by weight, up to 12% by weight, up to 11% by weight, up to 10% by weight, up to 9% by weight, up to 8% by weight, up to 7% by weight, up to 6% by weight, up to 5% by weight, up to 4% by weight, up to 3% by weight, up to 2% by weight, up to 1% by weight, up to 0.5% by weight, up to 0.3% by weight, up to 0.1% by weight, up to 500ppm, up to 300ppm, up to 100ppm, up to 50ppm, up to 40ppm, up to 30ppm, up to 20ppm or up to 10ppm. In another case, the composite metal halide can include a total impurity content of at least 0.2ppm by weight of the composite metal halide, such as at least 0.5ppm, at least 1ppm or at least 2ppm by weight of the composite metal halide. In another aspect, the total impurity content can be within a range including any of the minimum and maximum values ​​noted herein.

[0129] The content of the impurity phase can be determined as follows. Each impurity phase can be detected by XRD analysis coupled with Rietveld refinement for quantitative analysis by the presence of characteristic diffraction peaks corresponding to the parasitic phase. Rietveld refinement (RR) can analyze the shape and position of the peaks at the XRD pattern to quantitatively identify the contribution of each phase by collecting 2 data at the XRD diffraction at small increments of 2 angles and converting the XRD data into ratios of different phases.

[0130] For nitride-based impurity phases, LECO analysis can also be used to determine the presence and quantify the phase, especially when the nitride-based impurity phase is present in a molar or mass amount below 0.1%. LECO analysis is based on the combustion of the sample and the presence of nitrogen (or also sulfur, carbon, hydrogen, oxygen) is analyzed by the thermal conductivity or infrared absorption diagram of the boiled material gas.

[0131] In yet another aspect, the content of all nitride-based impurity phases (such as metal nitrides, metal oxynitrides and / or metal carbonitrides) present in the ion-conducting material is at most 0.5 weight percent of the weight of the composite metal halide, such as at most 0.3 weight percent, at most 0.2 weight percent, at most 0.1 weight percent, at most 500 ppm, at most 300 ppm, at most 100 ppm, at most 50 ppm, at most 40 ppm, at most 30 ppm, at most 20 ppm, or at most 10 ppm of the weight of the composite metal halide. In another case, the content of all metal nitrides can be at least 0.2 ppm of the weight of the composite metal halide, such as at least 0.5 ppm, at least 1 ppm, or at least 2 ppm of the weight of the composite metal halide. In another aspect, the content of all nitride-based phases can be within a range including any minimum and maximum values ​​mentioned herein.

[0132] In yet another aspect, the content of alkali halide (MX) can be up to 10 weight % of the weight of the composite metal halide, such as up to 9 weight %, up to 8 weight %, up to 7 weight %, up to 6 weight %, up to 5 weight %, up to 4 weight %, up to 3 weight %, up to 2 weight %, up to 1 weight %, up to 0.5 weight %, up to 0.3 weight %, up to 0.2 weight %, up to 0.1 weight %, up to 500 ppm, up to 300 ppm, up to 100 ppm, up to 50 ppm, up to 40 ppm, up to 30 ppm, up to 20 ppm or up to 10 ppm. In another case, the content of MX can be at least 0.2 ppm of the weight of the composite metal halide, such as at least 0.5 ppm, at least 1 ppm or at least 2 ppm of the weight of the composite metal halide. On the other hand, the content of MX can be within a range including any minimum and maximum values ​​mentioned herein.

[0133] In yet another aspect, the content of metal oxyhalide (MeOX) such as rare earth oxyhalide can be up to 5 weight % of the weight of the composite metal halide, such as up to 4 weight %, up to 3 weight %, up to 2 weight %, up to 1 weight %, up to 0.5 weight %, up to 0.3 weight %, up to 0.2 weight %, up to 0.1 weight %, up to 500 ppm, up to 300 ppm, up to 100 ppm, up to 50 ppm, up to 40 ppm, up to 30 ppm, up to 20 ppm or up to 10 ppm. In another case, the content of MeOX phase can account for at least 0.2 ppm of the weight of the composite metal halide, such as at least 0.5 ppm, at least 1 ppm or at least 2 ppm of the weight of the composite metal halide. On the other hand, the content of MeOX phase can be within the range of any minimum and maximum values ​​mentioned herein. In a specific aspect, the composite metal halide can be substantially free of MeOX.

[0134] In yet another aspect, the metal nitride Me x N k The content of the metal nitride can be up to 0.3% by weight of the weight of the composite metal halide, such as up to 0.1% by weight, up to 500ppm, up to 300ppm, up to 100ppm, up to 50ppm, up to 40ppm, up to 30ppm, up to 20ppm or up to 10ppm. In another case, the content of the metal nitride can be at least 0.2ppm by weight of the composite metal halide, such as at least 0.5ppm, at least 1ppm or at least 2ppm by weight of the composite metal halide. On the other hand, the metal nitride Me x N k The total content can be within a range including any of the minimum and maximum values ​​noted herein.

[0135] In yet another aspect, the metal nitride M x The content of N can be up to 0.3% by weight of the weight of the composite metal halide, such as up to 0.1% by weight, up to 500 ppm, up to 300 ppm, up to 100 ppm, up to 50 ppm, up to 40 ppm, up to 30 ppm, up to 20 ppm, or up to 10 ppm of the weight of the composite metal halide. In another case, the content of metal nitride can be at least 0.2 ppm by weight of the composite metal halide, such as at least 0.5 ppm, at least 1 ppm, or at least 2 ppm by weight of the composite metal halide. On the other hand, the total content of metal nitride MeN can be within a range including any minimum and maximum values ​​mentioned herein.

[0136] In the present disclosure, the total content of nitride-based phases and phases such as alkali nitrides and Me x N k The content of metal nitride can be detected by the following method. The ion conductive material can be dissolved in water, because the complex metal halide can be hygroscopic. The metal nitride is not hygroscopic and can be collected and analyzed after filtering the aqueous solution. X-ray diffraction analysis can be used to detect metal nitride content above 0.2 weight %. LECO content below 0.2 weight % can be used.

[0137] For the content of simple metal halides, the ion-conducting material can be analyzed using X-ray diffraction in the presence of dissolved ion-conducting material.

[0138] In certain cases, the solid ion conductive material may include NH3, NH4X, or a combination thereof, wherein X includes a halogen. In one example, NH3 and / or NH4X may exist as a separate phase in addition to the complex metal halide. In another example, NH3 and / or NH 4X It can be a dopant or impurity of a complex metal halide.

[0139] In yet another embodiment, the solid ion conductive material may include Li4(NH2)3Cl, Li7(NH2)6Cl, Li2Br(NH2), Li 13 [NH]6Cl, LiCl·NH3, LiBr·4NH3, or a combination thereof. In one instance, the one or more compounds may be present in a separate phase in addition to the complex metal halide. In another example, the one or more compounds may be byproducts produced by methods 100, 200, and / or 300. In another example, the compound may be a dopant or impurity present in the complex metal halide.

[0140] In one embodiment, the ion conductive material may have a bulk ionic conductivity of at least 0.01 mS / cm as measured by electrochemical impedance spectroscopy of a pellet sample sandwiched between ion blocking electrodes, such as at least 0.05 mS / cm, at least 0.08 mS / cm, or at least 0.1 mS / cm, or at least 0.3 mS / cm, or at least 0.5 mS / cm. In a specific example, the bulk ionic conductivity may be at least 0.6 mS / cm, at least 1.2 mS / cm, at least 1.8 mS / cm, or at least 2.2 mS / cm. In another example, the bulk ionic conductivity may be at most 15 mS / cm, at most 13 mS / cm, at most 11 mS / cm, at most 8 mS / cm, at most 7.2 mS / cm, or at most 6.2 mS / cm. In a specific example, the bulk ionic conductivity may be within a range including any of the minimum and maximum values ​​mentioned herein. Bulk ionic conductivity can be measured at room temperature, such as 22°C, and at activation energies in the range of 0.2 eV and 0.5 eV. In other cases, activation energies of 0 eV to 1 eV can be used for temperatures of 200°C to -80°C. For temperatures of 80°C to -30°C, the activation energy can be 0.1 eV to 0.6 eV. For temperatures above 0°C or below 10°C, the activation energy can be 0.1 eV to 0.5 eV.

[0141] In one embodiment, the solid electrolyte may include an ion conductive material. The ion conductive material may be a single crystal, a polycrystalline, or a combination thereof. The solid electrolyte may have improved ionic conductivity compared to a solid electrolyte comprising a conventionally formed composite lithium-based metal halide. In a specific example, the solid electrolyte may be composed of an ion conductive material. In a more specific example, the solid electrolyte may be composed of a single crystal composite metal halide, a polycrystalline composite metal halide, or an oriented crystallized composite metal halide, including a single crystal or an oriented ceramic with a specific crystallographic orientation. In a specific application, the electrolyte may include a crystallographically oriented solid ion conductive material, wherein the electrolyte may have a thickness extending in a direction parallel to the orientation of the solid ion conductive material.

[0142] In one embodiment, the composite ion conductive layer may include an ion conductive material and an organic material. The organic material may include a binder material, a polymer electrolyte material, or a combination thereof. In another example, the composite ion conductive layer may include a plasticizer, a solvent, or a combination thereof. Exemplary organic materials may include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), fluororubber, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, natural butyl rubber (NBR), paraffin, polypropylene carbonate, polyisobutylene, polyvinyl pyrrolidone, polymethyl methacrylate, poly(propylene oxide), polyvinyl chloride, poly(vinylidene fluoride), poly(acrylonitrile), poly(dimethylsiloxane), poly[bis(methoxyethoxyethanol salt)-phosphazene], polyvinyl carbonate, polypropylene glycol, polycaprolactone, poly(trimethylene carbonate), hydrogenated nitrile rubber, poly(ethylene vinyl acetate), high density polyethylene, low density polyethylene, polyurethane, or any combination thereof. In another example, the composite ion conductive layer may include a lithium salt. Exemplary lithium salts may include LiSbF6, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, LiAsF6, LiClO4, LiPF6, LiBF4, LiCF3SO3, or any combination thereof.

[0143] In another embodiment, the hybrid electronic and ion conductive layer may include an ion conductive material. In one aspect, the hybrid electronic and ion conductive layer may further include a cathode active material. Examples of cathode active materials may include, but are not limited to, lithium-containing transition metal oxides (such as Li(NiCoAl)O2 and LiCoO2), transition metal fluorides, polyanions and fluorinated polyanion materials, and transition metal sulfides, transition metal oxyfluorides, transition metal oxysulfides, transition metal oxynitrides, etc., or any combination thereof.

[0144] In another aspect, the mixed ion and electron conductive layer can include an anode active material. Exemplary anode active materials can include carbon materials such as artificial graphite, graphite carbon fiber, resin roasted carbon, pyrolysis vapor growth carbon, coke, mesophase carbon microbeads (MCMB), furfuryl alcohol resin roasted carbon, polyacene, pitch-based carbon fiber, vapor growth carbon fiber, natural graphite, non-graphitizable carbon, etc.; metal materials, including lithium metal, lithium alloys, etc.; oxides; nitrides; tin compounds; silicon compounds, or any combination thereof.

[0145] In some cases, the mixed ion and electronic conductive layer may include an electronic conductive agent. Examples of electronic conductive agents may include carbon fiber, carbon powder, stainless steel fiber, nickel-coated graphite, etc., or any combination thereof.

[0146] In one embodiment, a solid-state lithium battery may include an electrolyte disposed between an anode and a cathode. Figure 5 , showing a portion of a cross-section of an exemplary solid-state battery 500. Electrolyte layer 502 can be any of the electrolytes or composite layers mentioned in the embodiments of this document. Anode 504 covers electrolyte 502. In one embodiment, anode 504 may include a solid ion conductive material and an anode active material. In certain cases, anode 504 may be an anode of a 3-dimensional structure. In another embodiment, anode 504 may be a metal anode. For example, the anode may be composed of lithium. Cathode 506 may be disposed on the other side of electrolyte 506 opposite to anode 502. Cathode 506 may include a solid electrolyte material and an active cathode material. In certain embodiments, cathode 506 may be a cathode of a 3-dimensional structure.

[0147] In a specific example, the electrolyte 502 can be the single crystal wafer 302 shown in Figure 3. The anode 504 can overlie the major surface 304 shown in Figure 3. The major surface 306 is shown in Figure 3 and can be on the cathode 506.

[0148] Known techniques can be used to form an electrolyte, a composite ion conductive layer, an anode, a cathode or another component of a solid-state lithium battery having a solid electrolyte material. Such techniques include, but are not limited to, casting, molding, deposition, printing, pressing, heating, etc., or any combination thereof. In a particular embodiment, in order to form a multilayer structure, layers (such as an electrolyte and an anode and / or a cathode) can be formed separately and then laminated to form a multilayer structure. Alternatively, a stack of green electrolyte and an anode and / or cathode layer can be formed, which is then further processed (such as pressing, heating, drying or any combination thereof) to form the final multilayer structure.

[0149] In certain embodiments, a single crystal block or ingot may be processed together with cathode or anode active materials, such as by mechanical pressing or by heat activated co-extrusion to ensure intimate contact of the electrode with the electrolyte.

[0150] In another specific embodiment, single crystal blocks and single crystal ingots can be grown directly around particles of anode and / or cathode active materials to form a mixed electronic and ion conducting layer. In one aspect, the mixed ion and electronic conducting layer can include single crystal ion conducting materials, including inclusions containing anode or cathode active materials. In another aspect, the mixed ion and electronic conducting layer can include anode or cathode active materials densely packed within a single crystal ingot or single crystal block.

[0151] Many different aspects and embodiments are feasible. Some of those aspects and embodiments are described herein. After reading this specification, those skilled in the art will appreciate that those aspects and embodiments are merely illustrative and do not limit the scope of the invention. Embodiments may be based on any one or more embodiments listed below.

[0152] Example

[0153] Embodiment 1. A solid ion conductive material, the solid ion conductive material comprising a composite metal halide, wherein:

[0154] The complex metal halide is doped with a dopant comprising ammonium; and

[0155] The composite metal halide is composed of M 3-z (Me k+ ) f X 3-z+k*f represents, where:

[0156] -3≤z<3;

[0157] 2≤k<6;

[0158] 0≤f≤1;

[0159] M includes alkali metal elements;

[0160] Me includes a divalent metal element, a trivalent metal element, a tetravalent metal element, a pentavalent metal element, a hexavalent metal element, or any combination thereof; and

[0161] X includes halogen.

[0162] Embodiment 2. A solid ion conductive material, comprising:

[0163] The composite metal halide is composed of M 3-z (Me k+ ) f X 3-z+k*f represents, where:

[0164] -3≤z<3;

[0165] 2≤k<6;

[0166] 0≤f≤1;

[0167] M includes alkali metal elements;

[0168] Me includes a divalent metal element, a trivalent metal element, a tetravalent metal element, a pentavalent metal element, a hexavalent metal element, or any combination thereof; and X includes a halogen; and

[0169] Me is neutral in charge x N k or M x At least one of N, where x is the valence of N,

[0170] and k is the valence of Me.

[0171] Embodiment 3. The solid ion conductive material according to embodiment 1 or 2, wherein the composite metal halide is composed of (Li 1-d-e ,Na d ,M' e )2Li 1-z' (Me k+ ) f X 3+k*f-z represents, where:

[0172] 0≤d≤1;

[0173] 0≤e<1;

[0174] M consists of at least one of Li, Na and M'; and

[0175] M' consists of at least one of K, Rb and Cs.

[0176] Embodiment 4. A solid ion conductive material, the solid ion conductive material comprising (Li 1-d-e ,Na d ,M' e )2Li 1-z (Me k+ ) f X 3+k*f-z A complex metal halide represented by:

[0177] -3≤z<3;

[0178] 2≤k<6;

[0179] 0≤f≤1;

[0180] 0 <d≤1;

[0181] 0≤e<1;

[0182] M includes alkali metal elements;

[0183] Me includes a divalent metal element, a trivalent metal element, a tetravalent metal element, a pentavalent metal element, a hexavalent metal element, or any combination thereof; and X includes a halogen; and

[0184] Me is neutral in charge x N k or M x N, wherein x is the valence of N, and k is the valence of Me;

[0185] M consists of at least one of Li, Na, and M'; wherein M' consists of at least one of K, Rb, and Cs.

[0186] Embodiment 5. The solid ion conducting material of any one of embodiments 1 to 4, wherein z is between -0.95 and 0.95 and M consists of Na and Li.

[0187] Embodiment 6. A solid ion conductive material according to any one of embodiments 1 to 5, wherein Me includes one or more of rare earth elements, alkaline earth metal elements, 3d transition metals, Zn, Zr, Hf, Ti, Sn, Th, Ge, Ta, Nb, Mo, W, Sb, In, Bi, Al, Ga, Fe or any combination thereof.

[0188] Embodiment 7. The solid ion conducting material according to any one of embodiments 1 to 6, wherein Me comprises a rare earth element, Zr or any combination thereof.

[0189] Embodiment 8. The solid ion conducting material of any one of embodiments 1 to 7, wherein Me comprises Y, Ce, Gd, Er, Zr, La, Yb, In, Mg, Zn or any combination thereof.

[0190] Embodiment 9. A solid ion conducting material according to any one of embodiments 1 to 8, wherein X is composed of at least one of F, Cl, Br and I and an optional anionic group comprising -NH2(amide), -(NH) 0.5 (imide), -OH (hydroxide), -BH4 (borohydride), -BF4 group or any combination thereof.

[0191] Embodiment 10. The solid ion conducting material of any one of embodiments 1 to 9, wherein M consists of Gd, Y or a combination thereof.

[0192] Embodiment 11. The solid ion conducting material of any one of embodiments 1 to 9, wherein M consists of Ce, Y or a combination thereof.

[0193] Embodiment 12. The solid ion conducting material of any one of embodiments 1 to 9, wherein M consists of Er, Y or a combination thereof.

[0194] Embodiment 13. The solid ion conducting material of any one of embodiments 1 to 9, wherein M consists of Yb, Ce or a combination thereof.

[0195] Embodiment 14. The solid ion conducting material of any one of embodiments 1 to 9, wherein M consists of Y, Zr or a combination thereof.

[0196] Embodiment 15. The solid ion conducting material of any one of embodiments 1 to 9, wherein M consists of two or more of In, Y, Zr, Hf, Sc, Zn and Mg.

[0197] Embodiment 16. The solid ion conducting material of any one of embodiments 1 to 15, wherein the halogen consists of one of Cl, Br, I and F.

[0198] Embodiment 17. The solid ion conducting material of any one of embodiments 1 to 16, wherein the halogen consists of at least two or more of Cl, Br, I and F.

[0199] Embodiment 18. The solid ion conducting material of any one of embodiments 1 to 17, wherein the halogen consists of Cl, Br and I.

[0200] Embodiment 19. A solid ion conductive material according to any one of embodiments 1 and 4 to 18, wherein the complex metal halide is represented by Li3-zMek+X3-z+k, wherein Me includes a rare earth element, Zr or any combination thereof.

[0201] Embodiment 20. A solid ion conductive material according to any one of embodiments 1 to 18, wherein the composite metal halide is composed of (Li 1-d Na d )2Li 1-z Me k+ X 3+k-z It represents that Me includes rare earth elements, Zr or a combination thereof; and 0≤d<1, -0.95≤z=<0.95.

[0202] Embodiment 21. The solid ion conducting material of any one of embodiments 1 to 20, wherein z≤0.5 or z≤0.3 or z≤0.2.

[0203] Embodiment 22. The solid ion conducting material of any one of embodiments 2 to 21, wherein d ≥ 0.01 or d ≥ 0.05 or d ≥ 0.1.

[0204] Embodiment 23. The solid ion conducting material of any one of embodiments 2 to 22, wherein d≤0.8 or d≤0.5.

[0205] Embodiment 24. A solid ion conductive material according to any one of embodiments 1 to 9, wherein the composite metal halide is composed of (Li (1-d-e) ,Na (d) ,M' (e) )2Li (1-z') Me 3+ (1-u-p-q-r) Me 4+ (u) Me 2+ (p) Me 5+ (q) Me 6+ (r) (Cl (1-y-w) Br (y) I (w) ) (6+u-p+2q+3r-z') represents, where:

[0206] 0≤d≤1;

[0207] 0≤e<1;

[0208] -3≤z'<3;

[0209] M' includes at least one of K, Rb and Cs;

[0210] M 3+ Including rare earth elements, In, Bi, Sc, Y, Al, Ga or any combination thereof;

[0211] Me 4+ Zr 4+ , Hf 4+ 、Ti 4+ Sn 4+ ,Th 4+ ,Ge 4+ or any combination thereof;

[0212] Me 2+ Mg 2+ 、Zn 2+ , Ca 2+ , Sr 2+ , Ba 2+ , Yb 2+ 、Eu 2+ or any combination thereof;

[0213] Me 5+ For her 5+ , Nb 5+ , W 5+ , Sb 5+ or any combination thereof;

[0214] Me 6+ W 6+ 、Mo 6+ or any combination thereof;

[0215] 0<=w<=1;

[0216] 0<=y<=1;

[0217] -0.95 <z<0.95;

[0218] 0<=u<0.95;

[0219] 0<=p<0.95;

[0220] 0<=q<0.95; and

[0221] 0<=r<0.95.

[0222] Embodiment 25. The solid ion conducting material according to embodiment 24, wherein M 3+ Including Y 3+ , Gd 3+ 、In 3+ , Er 3 + ,La 3+ Sc 3+ or any combination thereof, where M 3+ By Y 3+ , Gd 3+ 、In 3+ , Er 3+ ,La 3+ Sc 3+ or any combination thereof.

[0223] Embodiment 26. A solid ion conducting material according to embodiment 24 or 25, wherein M 4+ Including Zr 4+ , Hf 4+ 、Ce 4+ or any combination thereof, where M 4+ By Zr 4+ , Hf 4+ 、Ce 4+ or any combination thereof.

[0224] Embodiment 27. A solid ion conducting material according to any one of embodiments 24 to 26, wherein:

[0225] p = 0;

[0226] q=0;

[0227] r = 0;

[0228] u=0; or

[0229] Any combination of them.

[0230] Embodiment 28. A solid ion conducting material according to any one of embodiments 1 to 9 and 24 to 27, wherein k=2 or 3 or 4 or 5.

[0231] Embodiment 29. A solid ion conductive material according to any one of embodiments 1 to 28, the solid ion conductive material comprising at least 10 ppm by mass of ammonium halide, based on the total weight of the composite metal halide, at least 100 ppm, at least 500 ppm, at least 0.1 wt%, at least 0.3 wt%, at least 0.5 wt%, at least 0.8 wt% or at least 1 wt% of ammonium based on the weight of the composite metal halide.

[0232] Embodiment 30. A solid ion conductive material according to any one of Embodiments 1 to 29, wherein the solid ion conductive material comprises up to 20 weight % of ammonium based on the total weight of the composite metal halide, and up to 15 weight %, up to 10 weight %, up to 8 weight %, up to 5 weight % or up to 3 weight % of ammonium based on the weight of the composite metal halide.

[0233] Embodiment 31. A solid ion conductive material according to any one of embodiments 1 to 30, further comprising a total content of simple metal halides of at most 0.5 weight % of the weight of the complex metal halide, at most 0.3 weight %, at most 0.1 weight %, at most 500 ppm, at most 300 ppm, at most 100 ppm, at most 50 ppm, at most 40 ppm, at most 30 ppm, at most 20 ppm or at most 10 ppm, based on the weight of the complex metal halide.

[0234] Embodiment 32. A solid ion conductive material according to embodiment 31, comprising at least 0.2 ppm of simple metal halide based on the total weight of the complex metal halide, at least 0.5 ppm or at least 1 ppm based on the total weight of the complex metal halide.

[0235] Embodiment 33. A solid ion conductive material according to embodiment 31 or 32, wherein the simple metal halide comprises an alkali metal halide, a rare earth halide or any combination thereof.

[0236] Embodiment 34. The ion-conducting material according to any one of embodiments 1 to 33, comprising at least 0.1 ppm by mass of charge-neutral Me based on the weight of the composite metal compound. x N k , and up to 10 ppm by mass of charge-neutral Me based on the weight of the composite metal compound x N k .

[0237] Embodiment 35. The ion-conducting material according to any one of embodiments 1 to 34, comprising at least 0.1 ppm by mass of charge-neutral M based on the weight of the composite metal compound. x N, and up to 10 ppm by mass of charge-neutral M based on the weight of the composite metal compound x N.

[0238] Embodiment 36. A solid ion conductive material according to any one of embodiments 1 to 35, comprising a bulk ionic conductivity of at least 0.001 mS / cm, at least 0.01 mS / cm, at least 0.1 mS / cm, at least 0.4 mS / cm, at least 0.8 mS / cm, at least 1.2 mS / cm, at least 1.8 mS / cm or at least 2.2 mS / cm.

[0239] Embodiment 37. A solid ion conductive material according to embodiment 36, comprising a bulk ion conductivity of at most 15 mS / cm, at most 13 mS / cm, at most 11 mS / cm, 8 mS / cm, at most 7.2 mS / cm or at most 6.2 mS / cm.

[0240] Embodiment 38. The solid ion conducting material of any one of embodiments 1 to 37, wherein the complex metal halide is in the form of a powder comprising an average particle size of at least 0.1 micrometer to 1 mm.

[0241] Embodiment 39. The solid ion conducting material according to any one of embodiments 1 to 38, wherein the solid conducting material is single crystal or polycrystalline.

[0242] Embodiment 40. The solid ion conducting material according to embodiment 39, wherein the solid ion conducting material is a single crystal or has <hkl>or <hklm>Represents the crystallographic orientation of the oriented polycrystal, where <hkl>or <hklm>The ionic conductivity at the crystallographic orientation is higher than that at different crystallographic orientations.

[0243] Embodiment 41. A solid ion conducting material according to embodiment 39 or 40, wherein the solid ion conducting material has a selected <100> and <001> The crystallographic orientation of the composed group.

[0244] Embodiment 42. The solid ion conductive material according to any one of embodiments 1 to 41, further comprising Li4(NH2)3Cl, Li7(NH2)6Cl, Li2Br(NH2), Li 13 [NH]6Cl, LiCl·NH3, LiBr·4NH3 or a combination thereof.

[0245] Embodiment 43. The solid ion conductive material according to any one of Embodiments 1 to 42, further comprising NH3, NH4X or a combination thereof.

[0246] Embodiment 44. A solid electrolyte layer comprising the solid ion-conducting material according to any one of embodiments 1 to 43.

[0247] Embodiment 45. A mixed electronic and ion conducting layer comprising a solid ion conducting material according to any one of embodiments 1 to 43, a cathode or an anode active material, and optionally an electronic conductive agent.

[0248] Embodiment 46. A solid-state lithium battery, comprising a solid-state electrolyte layer according to Embodiment 44.

[0249] Embodiment 47. A solid-state lithium battery comprising a hybrid electronic and ion conductive layer according to embodiment 45.

[0250] Embodiment 48. A solid electrolyte layer, the solid electrolyte layer comprising a single crystal material, the single crystal material comprising M 3-z (Me k+ ) f X 3-z+k*f A composite metal halide material represented by:

[0251] -3≤z<3;

[0252] 2≤k<6;

[0253] 0≤f≤1;

[0254] M includes alkali metal elements;

[0255] Me includes a divalent metal element, a trivalent metal element, a tetravalent metal element, a pentavalent metal element, a hexavalent metal element, or any combination thereof; and

[0256] X comprises a halogen; and

[0257] The single crystal material also includes charge-neutral Me x N k and M x N, wherein x is the valence number of N, and k is the valence number of Me.

[0258] Embodiment 49. A solid electrolyte layer, the solid electrolyte layer comprising an oriented crystal material, the oriented crystal material having a 3-z (Me k+ ) f X 3-z+k*f A composition wherein:

[0259] -3≤z<3;

[0260] 2≤k<6;

[0261] 0≤f≤1;

[0262] M includes alkali metal elements;

[0263] Me includes a divalent metal element, a trivalent metal element, a tetravalent metal element, a pentavalent metal element, a hexavalent metal element, or any combination thereof; and

[0264] X includes halogen.

[0265] Embodiment 50. The solid electrolyte layer according to Embodiment 49, wherein the oriented crystal material is an oriented ceramic or an oriented single crystal.

[0266] Embodiment 51. The solid electrolyte layer according to any one of Embodiments 48 to 50, wherein M comprises at least one of Li and Na.

[0267] Embodiment 52. The solid electrolyte layer of any one of Embodiments 48 to 51, wherein M consists of Li or a combination of Li and at least one of Na, Cs, Rb, and K.

[0268] Embodiment 53. A solid electrolyte layer according to any one of Embodiments 47 to 51, wherein the composition is composed of (Li 1-d ,Na d )2Li 1-z Me k+ X 3+k-z represents, where:

[0269] 0≤d<1;

[0270] -0.95≤z<=0.95;

[0271] 2≤k<6;

[0272] Me includes a divalent metal element, a trivalent metal element, a tetravalent metal element, a pentavalent metal element, a hexavalent metal element, or any combination thereof; and

[0273] X includes halogen.

[0274] Embodiment 54. A solid electrolyte layer according to any one of Embodiments 47 to 53, wherein Me includes rare earth elements and optionally alkaline earth metal elements, one or more of Zn, Zr, Hf, Ti, Sn, Th, Ta, Nb, Mo, W, Sb, In and Bi.

[0275] Embodiment 55. A solid electrolyte layer according to any one of embodiments 47 to 54, wherein Me includes Y, Ce, Gd, Er, Zr, La, Yb, In, Mg or any combination thereof.

[0276] Embodiment 56. A solid electrolyte layer according to any one of Embodiments 47 to 55, wherein X is composed of at least one of F, Cl, Br and I and an optional anionic group, the anionic group comprising -NH2(amide), -(NH) 0.5 (imide), -OH (hydroxide), -BF4 group or any combination thereof.

[0277] Embodiment 57. A solid electrolyte layer according to any one of embodiments 47 to 55, wherein Me is composed of Gd, Ce, Er, Yb, Zr, Y or any combination thereof.

[0278] Embodiment 58. The solid electrolyte layer according to any one of embodiments 47 to 55, wherein Me consists of Gd and optionally at least one of Ce, Er, Y and Zr.

[0279] Embodiment 59. The solid electrolyte layer according to any one of Embodiments 47 to 55, wherein Me consists of Yb and Ce.

[0280] Embodiment 60. The solid electrolyte layer according to any one of embodiments 47 to 55, wherein Me consists of Li and optionally at least one of Zr, Ce, Er and Gd.

[0281] Embodiment 61. A solid electrolyte layer according to any one of Embodiments 47 to 60, wherein the halogen consists of one of Cl, Br, I and F.

[0282] Embodiment 62. A solid electrolyte layer according to any one of Embodiments 47 to 61, wherein the halogen consists of at least two or more of Cl, Br, I and F.

[0283] Embodiment 63. A solid electrolyte layer according to any one of Embodiments 47 to 62, wherein the halogen consists of Cl, Br and I.

[0284] Embodiment 64. A solid electrolyte layer according to any one of Embodiments 47 to 63, wherein the composition is Li 3-z RE k+ X 3-z+k Represents, wherein RE includes rare earth elements, Zr or any combination thereof.

[0285] Embodiment 65. A solid electrolyte layer according to any one of Embodiments 47 to 64, wherein k=3 or 4 or 5.

[0286] Embodiment 66. A solid electrolyte layer according to any one of Embodiments 47 to 65, wherein the composition is composed of (Li (1-d) ,Na (d) )2Li (1-z) Me 3+ (1-u-p-q-r) Me 4+ (u) Me 2+ (p) Me 5+ (q) Me 6+ (r) (Cl (1-y-w) Br (y) I (w) ) (6+u-p+2q+3r-z) represents, where:

[0287] 0 <d<=1;

[0288] -0.95≤z<=0.95;

[0289] 0<=u<0.95;

[0290] 0<=p<0.95;

[0291] 0<=q<0.95;

[0292] 0<=r<0.95;

[0293] M 3+ Including rare earth elements;

[0294] Me 4+ Zr 4+ , Hf 4+ 、Ti 4+ Sn 4+ ,Th 4+ or any combination thereof;

[0295] Me 2+ Mg 2+ 、Zn 2+ , Ca 2+ , Sr 2+ , Ba 2+ , Yb 2+ 、Eu 2+ or any combination thereof;

[0296] Me 5+ For her 5+ , Nb 5+ , W 5+ , Sb 5+ or any combination thereof;

[0297] Me 6+ W 6+ ;

[0298] 0<=y<=1; and

[0299] w<=1.

[0300] Embodiment 67. The solid electrolyte layer according to embodiment 66, wherein M 3+ Including Y 3+ , Gd 3+ 、In 3+ , Er 3+ ,La 3 + or any combination thereof, where M 3+ By Y 3+ , Gd 3+ 、In 3+ , Er 3+ ,La 3+ or any combination thereof.

[0301] Embodiment 68. A solid electrolyte layer according to Embodiment 66 or 67, wherein M 4+ Including Zr 4+ 、Ce 4+ or any combination thereof, where M 4+ By Zr 4+ 、Ce 4+ or any combination thereof.

[0302] Embodiment 69. The solid electrolyte layer according to any one of Embodiments 63 to 68, wherein:

[0303] p = 0;

[0304] q=0;

[0305] u=0; or

[0306] Any combination of them.

[0307] Embodiment 70. A solid electrolyte layer according to any one of Embodiments 47 to 69, wherein z≤0.5 or z≤0.3 or z≤0.2.

[0308] Embodiment 71. A solid electrolyte layer according to any one of Embodiments 47 to 70, wherein d ≥ 0.01 or d ≥ 0.05 or d ≥ 0.1.

[0309] Embodiment 72. A solid electrolyte layer according to any one of Embodiments 47 to 71, wherein d≤0.8 or d≤0.5.

[0310] Embodiment 73. A solid electrolyte layer according to any one of Embodiments 47 to 72, wherein the crystalline material includes a total impurity content of at most 0.5 weight %, at most 0.2 weight %, at most 0.1 weight %, at most 500 ppm, at most 200 ppm, at most 100 ppm or at most 50 ppm, based on the total weight of the crystalline material.

[0311] Embodiment 74. A solid electrolyte layer according to Embodiment 73, wherein the impurity comprises a simple metal halide, the simple metal halide comprising a rare earth halide, an alkali halide, a charge neutral Me x N k , charge neutral M x N or any combination thereof.

[0312] Embodiment 75. A solid electrolyte layer according to any one of Embodiments 47 to 74, wherein the crystalline material comprises a total impurity content of at least 2 ppm based on the weight of the complex metal halide, at least 5 ppm or at least 10 ppm based on the weight of the crystalline material.

[0313] Embodiment 76. A solid electrolyte layer according to any one of Embodiments 47 to 75, wherein the crystalline material comprises at least 0.1 ppm by mass and at most 10 ppm by mass of charge-neutral Me based on the weight of the complex metal halide. x N k .

[0314] Embodiment 77. A solid electrolyte layer according to any one of Embodiments 47 to 76, wherein the crystalline material comprises at least 0.1 ppm by mass and at most 10 ppm by mass of charge-neutral M based on the weight of the complex metal halide. x N.

[0315] Embodiment 78. A solid electrolyte layer according to any one of Embodiments 47 to 77, wherein the crystalline material comprises Li4(NH2)3Cl, Li7(NH2)6Cl, Li2Br(NH2), Li 13 [NH]6Cl, LiCl·NH3, LiBr·4NH3 or a combination thereof.

[0316] Embodiment 79. A solid electrolyte layer according to any one of Embodiments 47 to 78, wherein the crystalline material comprises NH3, NH4X or a combination thereof.

[0317] Embodiment 80. A solid electrolyte layer according to any one of Embodiments 47 to 79, wherein the crystalline material comprises a bulk ionic conductivity of at least 0.01 mS / cm, at least 0.1 mS / cm, at least 0.2 mS / cm, at least 0.4 mS / cm, at least 0.5 mS / cm, at least 0.8 mS / cm, at least 1.2 mS / cm, at least 1.8 mS / cm or at least 2.2 mS / cm at 22°C, and an activation energy in the range of 0.01 eV and 0.5 eV, or wherein the crystalline material comprises an ionic conductivity of at most 15 mS / cm, at most 11 mS / cm, at most 9 mS / cm, at most 8 mS / cm, at most 7.2 mS / cm or at most 6.2 mS / cm.

[0318] Embodiment 81. The solid electrolyte layer of any one of Embodiments 1 to 80, comprising a thickness, wherein the thickness is <hkl>or <hklm>The crystallographic orientation extends, where <hkl>or <hklm>The ionic conductivity at the crystallographic orientation is higher than that at different crystallographic orientations.

[0319] Embodiment 82. The solid electrolyte layer according to embodiment 81, wherein the crystallographic direction is selected from <100> , <001> and <010> Composed of groups.

[0320] Embodiment 83. A solid electrolyte layer according to any one of Embodiments 47 to 82, wherein the single crystal material is in the form of a sheet.

[0321] Embodiment 84. The solid electrolyte layer of any one of Embodiments 1 to 83, comprising a thickness of 5 micrometers to 500 micrometers.

[0322] Embodiment 85. A method of forming a solid ion conducting material, the method comprising:

[0323] Formation (NH4) n Me k+ X 3+k , in which (NH4) is formed n Me k+ X 3+k It includes chemically replacing water in a hydrated salt containing REX3 with NH4X, wherein n>0; Me includes a rare earth element, Zr or a combination thereof; and X is one or more halogens.

[0324] Embodiment 86. The method according to embodiment 85 further comprises performing (NH4) n Me k+ X 3+k Solid state reaction with MX wherein M comprises an alkali metal.

[0325] Embodiment 87. The method according to embodiment 85 or 86, further comprising decomposing (NH4) n Me k+ X3+k.

[0326] Embodiment 88. The method according to any one of embodiments 85 to 87, further comprising forming a 3- z Me k+ X 3-z+k A solid ion conductive material of a complex metal halide represented by -3≤z<3; 2≤k<6; M includes at least one of Li and Na, wherein the solid ion conductive material includes a total impurity content of up to 0.5 weight % of the weight of the solid ion conductive material.

[0327] Embodiment 89. The method according to embodiment 88, wherein the impurity comprises Me k+ X k , MX or a combination thereof.

[0328] Embodiment 90. The method of any one of Embodiments 86 to 89, further comprising growing crystals comprising the complex metal halide.

[0329] Embodiment 91. The method according to any one of embodiments 85 to 90, further comprising forming a <010> , <100> and <001> The crystallographic orientation of the group consisting of the oriented crystalline material.

[0330] Embodiment 92. The method according to embodiment 90 or 91 further comprises growing a crystal from a melt, wherein the melt comprises a complex metal halide and an optional dopant material.

[0331] Embodiment 93. The method of any one of Embodiments 85 to 92, wherein the ion conductive material is a polycrystalline material.

[0332] Embodiment 94. The method of any one of Embodiments 85 to 93, wherein the ion conductive material comprises a charge neutral Me in an amount up to 0.5 wt % based on the weight of the ion conductive material. x N k ;

[0333] Embodiment 95. The method according to any one of embodiments 85 to 94, wherein the ion conductive material comprises Me in an amount of at least 0.1 ppm and at most 10 ppm by mass based on the weight of the ion conductive material. x N k .

[0334] Embodiment 96. The method of any one of Embodiments 85 to 95, wherein the ion conductive material comprises a charge neutral M in an amount up to 0.5 wt % based on the weight of the ion conductive material. x N.

[0335] Embodiment 97. The method of any one of embodiments 85 to 96, wherein the ion conductive material comprises a charge neutral M in an amount of at least 0.1 ppm and at most 10 ppm by mass based on the weight of the ion conductive material. x N.

[0336] Embodiment 98. The method according to any one of embodiments 85 to 97, wherein the ion conductive material further comprises forming Li4(NH2)3Cl, Li7(NH2)6Cl, Li2Br(NH2), Li 13 [NH]6Cl, LiCl·NH3, LiBr·4NH3 or a combination thereof.

[0337] Embodiment 99. A method according to any one of embodiments 85 to 97, wherein the ion conductive material further comprises NH3, NH4X or a combination thereof.

[0338] Examples

[0339] Example 1

[0340] Samples 1 to 30 were formed having the compositions indicated in Table 1. The impurity contents of the simple metal halides are included in Table 1, and each impurity phase was detected by XRD analysis coupled with Rietveld refinement for quantitative analysis by the presence of characteristic diffraction peaks corresponding to the parasitic phase.

[0341] All samples contained metal nitrides up to 10 ppm.

[0342] Samples 1, 2, 4 to 6, 15, 17 and 30 are pressed ceramic pellets, and are heated under dry inert conditions. Except sample 6, pellets are formed according to the wet ammonium route described in the embodiments of this paper. Sample 6 is formed by using the one-step molding method described in the embodiments of this paper. The pellets are 5mm to 13mm (diameter) by 0.5mm to 4mm (thickness). Samples 8 to 14 and 18 to 29 are cut from the single crystal formed according to the embodiments of this paper. For the formation of samples 20, 21 and 23, LiCl, LiBr and LiI salts are also used as additives for the starting material charge of the anion-substituted compound crystal growth.

[0343] The ionic conductivity of the samples was determined using electrochemical impedance spectroscopy with a gold blocked electrode at room temperature (about 22° C.) under conditions of AC frequency ranging from 3 MHz to 10 Hz and a peak-to-peak sinusoidal AC voltage signal ranging from 10 mV to 50 mV.

[0344] The ionic conductivity of the bulk grains in samples 1, 2, 4 to 6, 15, 17, and 30 is included in Table 1. The conductivity contribution from the bulk grains can be distinguished from the grain boundaries and electrode contacts because the conductivity features of the bulk grains appear at the highest frequencies and are associated with the lowest values ​​of the double layer capacitance.

[0345] For sample 3, neither direction A nor direction B corresponds to the orientation that indicates the maximum thermal and / or ionic conductivity of Li3YCl6. Slicing along direction A produces a ceramic sample with grains in a random crystallographic orientation. Direction A can be determined by the vector a, where a = α* <100> +β* <010> , and where -1.0<α<1.0 and -1.0<β<1.0. Slicing along direction B produces an orientation close to <001> Crystallographically oriented ceramic samples.

[0346] Table 1

[0347]

[0348]

[0349]

[0350]

[0351] Example 2

[0352] A Li3YB6 polycrystalline block having a cylindrical shape and a size of 7 cm x 10 cm was formed. The block consisted of dense single crystals of millimeter to centimeter size and arranged in a mica-like layered orientation. The bulk ionic conductivity was measured on a small block broken from the center of the block. The small block was polished into parallel samples of approximately 0.7 mm thickness and the impedance was measured in the same manner as described in Example 1. Depending on the orientation of the selected sample, the impedance was approximately 0.5 mS / cm or 2.5 mS / cm. XRD analysis confirmed that the two samples had different crystallographic orientations.

[0353] The grains of the first sample are mainly (more than 80%) along the crystallographic direction <100> The second sample is shown to be a randomly oriented grain, where the crystallographic orientation is attributed to <001> Orthogonal planes;

[0354] Example 3

[0355] Crystalline pure material was ground using an automated pestle and mortar grinder. This low energy grinding preserves the purity of the material. The same material was ground in a high energy ball mill and partial decomposition of the pure material was observed as indicated by the appearance of small signatures of simple halides in the XRD analysis. The conductivity of the decomposed powder was lower than that of the pure powder or oriented crystals / ceramics.

[0356] Example 4

[0357]

[0358]

[0359] Note that high-energy ball milling synthesis can generate synthesis reactions in parallel and can also decompose the main complex metal halide phase. Compared with the method of the embodiment of this article, high-energy ball milling synthesis can generate significantly higher content of simple compounds such as LiX and YX3, which exist as impurities near the main Li3YX6 phase.

[0360] It is also noted that starting from an oxide (Y2O3) or carbonate material (Li2CO3), and adding ammonium halide in a solid-state reaction at 1 bar atmospheric pressure, it may not be possible to synthesize a single phase of Li3YX6. When the rare earth metal (i.e., Y in the Li3YX6 example) is converted to a halide compound, at least two chemical reactions can occur. One main reaction can lead to the synthesis of YX3, which can further react to form the Li3YX6 phase. The second reaction can lead to the formation of YOX. YOX is a stable compound and can be present as an impurity in the final product Li3YX6.

[0361] Example 5

[0362] Additional samples were formed. Sample 35 was synthesized by using a stoichiometric mixture of LiBr and YBr3 compounds in a welded quartz tube heated to 650°C under vacuum. After the reaction mixture was melted, a soak time of up to one hour was applied at 650°C to ensure that the reaction products were dissolved in the self-flux. The temperature of the quartz tube was then quickly (within 2 to 3 minutes) reduced to 400°C to help minimize partial decomposition of the inconsistent Li3YBr6 phase. The temperature of the quartz tube was then gradually reduced to room temperature at a rate of 50°C / hour to 100°C / hour.

[0363] Samples 36 and 37 are actively retained ammonium synthesized according to the examples herein. The amount of residual ammonium is estimated by post-heating the compound to a melting temperature that allows complete sublimation of the ammonium halide from the feed. The bulk ionic conductivity of the samples was measured in a similar manner as described in Example 1.

[0364]

[0365] The benefits, other advantages and solutions to the problems have been described above with reference to specific embodiments. However, the benefits, advantages, solutions to the problems and any features that may make any benefit, advantage or solution conceivable or more significant are not considered to be key, required or essential features of any or all claims. The materials mentioned herein including one or more components may be interpreted as including at least one embodiment in which the material is substantially composed of the specified one or more components. The term "substantially composed of..." should be interpreted as including ingredients that include those materials specified and exclude all other materials except for a small amount of materials (e.g., impurity content) that do not significantly change the properties of the material. In addition or alternatively, in certain non-limiting embodiments, any of the compositions specified herein may be substantially free of materials that are not explicitly disclosed. The embodiments herein include content ranges of certain components within the material, and it should be understood that the content of the components within a given material totals 100%.

[0366] The description and illustration of the embodiments described herein are intended to provide a general understanding of the structure of various embodiments. The description and illustration are not intended to be used as a detailed and comprehensive description of all elements and features of the device and system using the structure or method described herein. A separate embodiment may also be provided in a combined manner in a single embodiment, and conversely, the various features described in the context of a single embodiment for simplicity may also be provided individually or in any sub-combination. Further, references to values ​​represented by ranges include each value and all values ​​within the range. Only after reading this specification, many other embodiments will be apparent to the technician. Other embodiments may be utilized and obtained by the present disclosure, so that structural replacement, logical replacement or other changes may be performed without departing from the scope of the present disclosure. Therefore, the present disclosure should be considered illustrative and not restrictive.< / hklm> < / hkl> < / hklm> < / hkl> < / hklm> < / hkl> < / hklm> < / hkl> < / hklm> < / hkl> < / hklm> < / hkl>

Claims

1. A solid ion conducting material, comprising a crystallographically oriented ceramic material, wherein the crystallographically oriented ceramic material has grains composed of <hkl>or <hklm>The crystallographic orientation represented by M is oriented, and the crystallographic orientation ceramic material includes 3-z (Me k+ ) f X 3-z+k*f represents a halide material, where:< / hklm> < / hkl> -3≤z<3; 2≤k≤6; 0<f≤1; M includes an alkali metal element, and the alkali metal element includes Li; Me includes a divalent metal element, a trivalent metal element, a tetravalent metal element, a pentavalent metal element, a hexavalent metal element or any combination thereof; X comprises a halogen; and The halide material includes at least two different cations, Among them <hkl>or <hklm> The ionic conductivity at the crystallographic orientation is higher than that at different crystallographic orientations.< / hklm> < / hkl> 2. The solid ion conductive material according to claim 1, wherein the halogen is one or more elements selected from the group consisting of Cl, Br and F.

3. The solid ion conductive material according to claim 1, wherein Me comprises rare earth elements, Zn, Zr, Hf, Ti, Sn, Sb, In, Bi, Fe, Al, alkaline earth metal elements or any combination thereof.

4. The solid ion conductive material according to any one of claims 1 to 3, wherein the halide material is Li 3- z Me k+ X 3-z+k Represents that Me includes rare earth elements, Al, Zr, Hf, In, Mg, Zn or any combination thereof.

5. The solid ion conducting material according to claim 1, wherein more than 80% of the grains are formed along <hkl>or <hklm> Orientation is performed according to the crystallographic orientation indicated.< / hklm> < / hkl> 6. A solid ion conductive material, comprising a crystallographically oriented ceramic material, wherein the crystal grains of the crystallographically oriented ceramic material are oriented in a specific direction, and the crystallographically oriented ceramic material comprises (Li 1-d-e ,Na d ,M' e )2Li 1-z (Me k+ ) f X 3+k*f-z represents a halide material, where: -1≤z<1; 2≤k<6; 0<f≤1; 0≤d≤1; 0≤e<1; (d+e+f)>0; Me includes rare earth elements, Zn, Zr, Hf, Ti, Sn, Sb, In, Bi, Fe, alkaline earth metal elements, or any combination thereof; and X includes halogen; and M' consists of at least one of K, Rb and Cs, wherein Li accounts for at least 50 mol% of the total content of Li, Na and M'.

7. The solid ion conductive material according to claim 6, wherein the halide material is Li 3-z (Me k+ ) f X 3-z+k*f It represents that X includes at least one of Cl or Br.

8. The solid ion conducting material of claim 6, wherein the crystallographically oriented ceramic material has <hkl>or <hklm>Represents the crystallographic orientation, where <hkl>or <hklm> The ionic conductivity at the crystallographic orientation is higher than that at different crystallographic orientations.< / hklm> < / hkl> < / hklm> < / hkl> 9. A solid ion conducting material according to any one of claims 1 to 3 and 6 to 8, wherein the halide material comprises: A total MX content of up to 3 wt% based on the weight of the halide material; a charge-neutral Me x N k or M x N, wherein x is the valence of N and k is the valence of Me; or any combination thereof.

10. A solid electrolyte layer, comprising a crystallographically oriented crystal material, wherein the crystallographically oriented crystal material comprises (Li 1-d-e ,Na d ,M' e )2Li 1-z (Me k+ ) f X 3+k*f-z represents a halide material, where: -3≤z<3; 2≤k<6; 0≤f≤1; -3≤z<3; 2≤k≤6; 0≤f≤1; 0≤d≤1; 0≤e<1; (d+e)≥0; M' consists of at least one of K, Rb and Cs; Me includes a divalent metal element, a trivalent metal element, a tetravalent metal element, a pentavalent metal element, a hexavalent metal element or any combination thereof; X comprises a halogen; and The halide material includes at least two different cations, The crystallographic orientation of the crystal material is along the thickness direction of the solid electrolyte layer, and the ionic conductivity in the crystallographic orientation is higher than that in different crystallographic orientations.

11. The solid electrolyte layer according to claim 10, wherein the halide material is Li 3-z (Me k+ ) f X 3-z+k*f It represents that X includes at least one of Cl or Br. 12 . The solid electrolyte layer according to claim 10 , wherein the crystallographically oriented crystalline material is a ceramic material including grains having a crystallographic orientation along a thickness direction of the solid electrolyte layer.

13. The solid electrolyte layer according to claim 10, wherein the crystallographically oriented crystalline material is a single crystalline material.

14. The solid electrolyte layer according to any one of claims 10 to 13, wherein the solid electrolyte layer comprises: The total content of alkali metal halides is up to 3% by weight of the halide material; the charge-neutral Me x N k or M x N, wherein x is the valence of N and k is the valence of Me; or any combination thereof.

15. The solid electrolyte layer according to claim 10, wherein when (d+e)>0, Li accounts for at least 50 mol% of the total content of Li, Na and M'.